A Systematic Review of the Preventive and Therapeutic Effects of Naringin Against Human Malignancies - Ghanbari-Movahed, Maryam; Jackson, Gloria; Farzaei, Mohammad Hosein; Bishayee, Anupam (Frontiers in Pharmacology, 2021)
Background: Natural product-based cancer preventive and therapeutic entities, such as flavonoids and their derivatives, are shown to have a noticeable capability to suppress tumor formation and cancer cell growth. Naringin, a natural flavanone glycoside present in many plant species, has been shown to modulate various signaling pathways and interact with numerous cell signaling molecules, which allows for an extensive variety of pharmacological actions, such as amelioration of inflammation, oxidative stress, metabolic syndromes, bone disorders, and cancer. The aim of this systematic review is to present a critical and comprehensive assessment of the anticancer ability of naringin and associated molecular targets in various cancers. Methods: Studies were identified through systematic searches of Science Direct, PubMed, and Scopus as well as eligibility checks according to predefined selection criteria. Results: Eighty-seven studies were included in this systematic review. There was strong evidence for the association between treatment with naringin alone, or in combination with other drugs and anticancer activity. Additionally, studies showed that naringin-metal complexes have greater anticancer effects compared to free naringin. It has been demonstrated that naringin employs multitargeted mechanisms to hamper cancer initiation, promotion, and progression through modulation of several dysregulated signaling cascades implicated in cell proliferation, apoptosis, autophagy, inflammation, angiogenesis, invasion, and metastasis. Conclusion: The results of our work show that naringin is a promising candidate for cancer prevention and treatment, and might offer substantial support for the clinical application of this phytocompound in the future. Nevertheless, further preclinical and clinical studies as well as drug delivery approaches are needed for designing novel formulations of naringin to realize the full potential of this flavonoid in cancer prevention and intervention.